ECONOMIC ETHICS IN THE PERSPECTIVE OF RELIGIOUS EDUCATION: BETWEEN MORALITY AND PROFIT - Sahruddin Sahruddin (Adisam Publisher, 2025)
This study discusses economic ethics in the perspective of religious education with a focus on the balance between morality and profit orientation. Amidst the dynamics of modern economics that emphasise efficiency and profit, religious education plays an important role in instilling ethical values such as honesty, justice, and social responsibility. The research method used is a literature study with qualitative descriptive analysis, examining literature on the concept of economic ethics in various religious traditions and contemporary business practices. The results of the study show that religious education can be the foundation for shaping the character of economic actors so that business decisions are not only profit-oriented but also oriented towards the common good. The integration of moral and religious ethical principles into economic activities is believed to be capable of creating sustainable, fair, and civilised business practices. These findings emphasise the important role of educational institutions and economic stakeholders in strengthening religious values to balance material interests and moral responsibilities in the era of globalisation.